Adiponectin and Exercise: a Scientometric Analysis - Morales Osorio, Brandon; Quenan, Yoccner (Revista Cubana de Información en Ciencias de la Salud, 2025)
The objective of the present study is to analyze the field of application of Adiponectin, physical exercise, and their derivable aspects in healthy individuals and those with pathologies. The methodology used was developed based on an exploratory analysis of descriptive and inferential data, using the Science Tree algorithm for a field search within the Web of Science (WoS) and Scopus databases. Initial results indicate the existence of roots corresponding to classical topics in the field of Adiponectin and its relationship with insulin sensitivity, as it is a hormone that mitigates the spread of metabolic and cardiovascular diseases. The trunk refers to Adiponectin synthesis versus different types of exercise training, demonstrating a close relationship between physical exercise and Adiponectin depending on the type of training. The leaves represent three branches that bifurcate towards specific topics such as the relationships evident between Adiponectin and physical exercise, the optimization of physical exercise interventions to increase Adiponectin levels, and the physiological effects in the presence of exercise and diet in healthy individuals and those with underlying pathologies. It can be concluded that the total citation network contains highly relevant articles of interest to healthcare professionals. Future studies may indicate the need and interest in improving physical exercise interventions in association with other protective factors to increase Adiponectin levels in humans.